Maidenhead to Conventicle: The Curious Transformation of a Woodcut. (17th March 2020) - Williams, William Proctor
Abstract: Thomas Heywood's play A Maidenhead Well Lost (1634), printed by Nicholas Okes, has a woodcut larger than the usual page size for this quarto on its title-page and later in the book. It was clearly devised for this book only. Aside from this curious fact, the woodcut, considerably modified, was used later in John Taylor's polemical The Brownists conventicle (1641) which was not printed by Okes who was dead by then. Although the existence of this woodcut is noted by scholars, notably Greg and Foakes, it has never been given careful bibliographical study. This paper provides such a study and considers the curious use of the woodcut in both books.